PENGARUH PENERAPAN MODEL PEMBELAJARAN COPERATIVE LEARNING TEKNIK JIGSAW TERHADAP HASIL BELAJAR SEJARAH SISWA PADA MATERI POKOK PERJUANGANGAN PERGERAKAN PEMUDA INDONESIA DI KELAS XI SMA NEGERI 1 TUKKA TAPANULI TENGAH - Manahan Simatupang (Jurnal TAROMBO, 2019)
Is seen from result learn the student of Class of XI SMA Negeri 1 Tukka of direct material of struggle of Movement of Young fellow of Indonesia still lower or not yet reached the complete criterion of minimum, from the background of researcher do/conduct the research as a mean to know whether/what there is influence model the study of Cooperative Learning of Technique Jigsaw to result learn the student of direct material of struggle of movement of young fellow of Indonesia in class of X SMA Negeri 1 Tukka. Place And this research time is executed in SMA Country 1 Middle Tukka by using method experiment. Population in this research is Class of XI SMA Negeri 1 Tukka 2013 / 2014 consisted of consisted of by 6 class with the amount 216 people with the Technique of intake sample conducted by random sampling with the amount of sample research amount to 45 people, later; then in test with the test t-tes. From calculation to second of variable obtained by using Equate and test, Average value from type Jigsaw is equal to 2,76 be at the category " Whether". Mean of result of learning student history of at direct material of struggle of movement of Young fellow of Indonesia of before use model the study of cooperative learning of type jigsaw is 67.40 be at the category " enough" and While mean of result of learning student history of at direct material of struggle of movement of Young fellow of Indonesia hereafter use model the study of cooperative learning of type jigsaw is 78,48 be at the category " Whether". Calculation Result obtained by tcount of equal to 6.371. If compared to by ttable of belief level 95% or mount the mistake 5% with the degree of freedom (dk) = N - 2 = 45 - 2 = 43 equal to 2.02. Knowable thereby that value tcount of bigger than at ttable (6.371> 2.02). Pursuant to the value comparison result, hence acceptable alternative hypothesis or agreed. Its meaning " There are is influence model the study of Cooperative Learning of Technique Jigsaw to result learn the student of at direct material of struggle of movement of young fellow of Indonesia in class of X SMA Negeri 1 Tukka.